(untitled) (Ecolinguística: Revista brasileira de ecologia e linguagem (ECO-REBEL), 2016)
C. FERRARIZI JÚNIOR; MOLLICA, M.C (orgs.). Sociolinguística, Sociolinguísticas: Uma introdução. São Paulo: Editora Contexto, 2016.